+0  
 
0
341
1
avatar+4 

2y-3x=4, 3y-3x=1

umiemalais  Apr 20, 2017
 #1
avatar+93691 
+1

2y-3x=4   (1)

 3y-3x=1    (2)

 

(2)-(1)

3y-2y-3x--3x=1-4

y=-3

y=-3

 

sub into (1)

2*-3-3x=4

-6-3x=4

-3x=10

x=-10/3

 

so

x=-10/3      y=-3

 

check by subbing into (2)

LHS=3*-3   -   3*-10/3 = -9+10 = 1 = RHS   excellent :)

Melody  Apr 20, 2017

31 Online Users

avatar

New Privacy Policy

We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive information about your use of our website.
For more information: our cookie policy and privacy policy.